THE DISTINCTIVE FEATURES OF AUSTRALIAN ENGLISH - Bokieva Muharramoy Ne'matjon kizi (TADQIQOTLAR, 2025)
Australian English (AusE) represents a unique variant of the English language, shaped by historical, cultural, and social influences. This study examines the phonological, lexical, and syntactic characteristics of AusE, highlighting its distinctiveness from other English varieties. Through a systematic review of linguistic data and sociolinguistic analysis, the research identifies key features such as vowel shifts, unique vocabulary, and informal syntactic structures. The findings underscore AusE’s role as a dynamic and evolving dialect, reflecting Australia’s multicultural identity.